Magnitudes of Immunization Dropout Rate and Predictors for 12-23 Months Aged Children in Abobo District Southwest Ethiopia - Kassaw, Ayalew; Mariam, Abebe Gebere; Kebede, Alemi; Kebede, Fassikaw (International Journal of Child Health and Nutrition, 2022)
Vaccination is the epicenter of preventive care for good children’s health outcomes in each nation. Nevertheless, a number of factors have been hindering the attainment of targets from providing complete vaccination in different nations. This study aims to assess predictors of immunizations in 12-23 months aged children in Abobo District, Gambela regions southwest Ethiopia. Method: A community-based cross-sectional study was employed in 436 pairs of mothers to children aged 12–23 months from 12 marches—27 April 2019. The study participant was recruited by multistage-sampling were used for each kebele. Data were entered into Epi-Data version 3.1 after cleaning and coded, exported to STATA/SE-14/R logistic regression analysis. Variables with P-value <0.25 in bivariate logistic regression were transported into multivariable logistic regression. A variable with 95%CI in AOR was used as claim predictors for the dropout rate. Results: The overall dropout rate of immunization from completion was found 25.8% (95%CI: 21.5–30.2). Factors like mothers did not attend ANC (AOR= 4.59, 95% CI: 2.58, 7.84), being home delivery (AOR=6.46, 95% CI: (3.5— 11.4), postponed last immunization scheduled (AOR=3.44, 95% CI: 1.98—5.97), children ill during measles vaccine (AOR=1.83, 95% CI: (1.02—3.28), Mothers refused ≥30 minutes for vaccine service waiting (AOR=3.58, 95% CI: (1.99, 6.44) were significantly associated with immunization dropout out. Conclusion: The immunization dropout rate was unacceptable and higher compared to WHO reference (<10%). Home delivery postponed measles vaccine, child illness, ANC status Service refusal ≥30 minutes waiting for the vaccine were independently associated with dropout.